Designing Toll Road Concessions : Lessons from Argentina - Estache, Antonio; Carbajo, Jose (World Bank, Washington, DC, 2012)
Argentina began to concession its intercity highways and the access roads to Buenos Aires in the early 1990s. It first offered the intercity highways for competitive bids, setting the terms, the tolls, and the service levels and basing bid selection primarily on the rental offered for the infrastructure. When it concessioned the access roads in a second round, it set the terms and the investments and selected the bid offering the lowest tolls. The results so far have been mixed. Investment has lagged, but maintenance of the intercity highways has improved. The authors review the lessons from this experience and identify some of the challenges for future concessions: following clear and simple rules in the bidding process, establishing clear rules for renegotiation, and strengthening regulatory capacity.